O meu Reino não é deste mundo (Jo 18,36): o Reino de Deus no quarto Evangelho - Silva, Weliton Angelino da (2021)
This research aims to investigate the theme of the Kingdom of God in the Gospel of John through the exegesis of the pericope 18,28-38. The objective is to demonstrate that the theme of the Kingdom of God, in the Johannine text, is closely linked to Christ as a revelator of the divine glory and sent by the Father. To present Jesus as such, the Joanine community used the rich theology of Messianism and the Kingdom of God contained in the First Testament, especially since the period of the second Temple. The first chapter places the micronarrative within its co-text - which is the account of the condemnation of Jesus to death by Pilate (18,1- 19,16a) - and carries out the common steps of exegetical methodology, in order to go through the various nuances of biblical research. In the second chapter, the construction of the theme of the Kingdom of God in the economy of salvation is explored, starting from the dramatic fall of the Davidic throne, and, finally, the micronarrative 18,28-38 is analyzed, under the synchronic perspective of the approach narrative, which is considered the vanguard in current biblical studies